Characterization and heavy metal contamination assessment of sediments in Bued River - Macasieb, Reygie Q.; Tapales, Ben Joseph M.
Sediments may become a source of information and carrier of heavy metal transport as heavy metals are adsorbed by sediment particles. The role of these sediments in the transport of heavy metals was investigated in this study. The quality of sediments was also assessed using existing standards abroad because of the lack of sediment quality standards in the Philippines. Sediment samples were taken from 10 sites along the Bued River for two months (November and December). The detected concentrations of heavy metals decreases in the order of Pb>As>Hg and values ranges from 0.1-2646.24 mglkg for Pb, 4.14-30.47 mg/kg for As, and 0.004-0.373 mg/kg for Hg. The sediments were also characterized by their physico-chemical characteristics and correlated with the measured heavy metal content to determine its effect in the attachment and transport of heavy metals in sediments. The sediment samples obtained were primarily composed of sandy particles (~90% of dry weight), pH level is mostly basic (6.8-8.5) and specific gravity ranges from 2.21 to 3.36. It was found that for the case of Bued River, Pb and As tend to attach more to finer particles while there was no significant correlation between Hg and fine particles. Specific gravity and pH level on the other hand has no direct influence in the attachment of heavy metals to sediment particles. Moreover, using the Australian and New Zealand Standard and the Ontario Ministry of Environment Screening Guidelines, it was found that the contamination level of As and Hg is low to moderate while the level of Pb is moderate to high.